2012
DOI: 10.1111/mmi.12025
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of substrate specificity and biochemical properties of the sn‐glycerol‐3‐phosphate ATP binding cassette transporter (UgpBAEC2) of Escherichia coli

Abstract: SummaryUnder phosphate starvation conditions, Escherichia coli can utilize sn-glycerol-3-phosphate (G3P) and G3P diesters as phosphate source when transported by an ATP binding cassette importer composed of the periplasmic binding protein, UgpB, the transmembrane subunits, UgpA and UgpE, and a homodimer of the nucleotide binding subunit, UgpC. The current knowledge on the Ugp transporter is solely based on genetic evidence and transport assays using intact cells. Thus, we set out to characterize its properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 52 publications
(92 reference statements)
8
45
0
Order By: Relevance
“…This can be ascribed to some extent to the fact that GlpT is a G3P importer at the price of simultaneously being a phosphate exporter (63). In agreement with this notion, previous studies suggested that Glp-transported G3P can serve as the sole source for both carbon and phosphate, whereas Ugp-transported G3P can serve as the sole source only for phosphate (62,64). Thus, we believe that Ugp induction is mostly driven by phosphate starvation, whereas the Glp repression is likely due to unavailability of G3P as a carbon source as well as to phosphate limitation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This can be ascribed to some extent to the fact that GlpT is a G3P importer at the price of simultaneously being a phosphate exporter (63). In agreement with this notion, previous studies suggested that Glp-transported G3P can serve as the sole source for both carbon and phosphate, whereas Ugp-transported G3P can serve as the sole source only for phosphate (62,64). Thus, we believe that Ugp induction is mostly driven by phosphate starvation, whereas the Glp repression is likely due to unavailability of G3P as a carbon source as well as to phosphate limitation.…”
Section: Discussionsupporting
confidence: 70%
“…As one of two major sn-glycerol-3-phosphate (G3P) uptake systems, the ugp operon is often induced when bacteria are starved for inorganic phosphate (62). Interestingly, while the Ugp system was induced in response to phosphate limitation, the other G3P transporter, the Glp system, was significantly repressed at 6 h postinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility would be that G2P is converted into G3P in the periplasm and only then is transported by Ugp. This may be in agreement with a recent report that challenged the notion that Ugp is able to take up G2P in vitro (23). However, a periplasmic enzyme that catalyzes the conversion of G2P to G3P is still unknown.…”
Section: Discussionsupporting
confidence: 81%
“…PWBP57 has a two-domain structure containing an N-terminal UgpB domain and a C-terminal conserved domain of unknown function (DUF3502). The UgpB protein, a member of the SBP superfamily, binds to sn-glycerol-3-phosphate and is structurally similar to SBPs (29). Sequence identity (in amino acid residues) was 13 to 32% among the SBP domains of PWBPs.…”
Section: Resultsmentioning
confidence: 99%
“…The UgpB domain belongs to cluster B in the SBP superfamily and is structurally similar to SBPs (29). Most SBPs with specific binding to saccharides are classified in cluster B and are a component of ATP-binding cassette (ABC) transporters for substrate uptake.…”
Section: Discussionmentioning
confidence: 99%